IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS PADA MATERI LINGKARAN KELAS VIII - Prima Novia Agustini; Nila Kesumawati; Ismi Yuliana (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The purpose of this class action research is to define the implementation of the problem based learning model to improve the mathematical reasoning ability of the students of the eighth grade Fatimah Azzahra SMP IT Izzudin Palembang 2023/2024 on circular material. Execution of research using two cycles, each cycle has steps namely planning, action, observation, and reflection. Data collection on this study uses observation, and testing. The research was carried out with the participation of 17 students of the eighth grade at Izzudin Palembang IT High School. The aim of this study is to apply the learning model of problem based learning with the aim of improving the ability of mathematical reasoning of students. Students experience improvement in every aspect. The increase in the percentage of students' scores in mathematical reasoning skills during the first cycle reached 61.91%, while in the second cycle increased by 84.03%. The implementation of this study uses the pre-cycle phase by giving pre-test questions so that students reached the percent of 43.13% and in the post-test phase students achieved 80.84% so that it can be concluded that each indicator of mathematic reasoning ability students experienced a good improvement.